Massive die-offs of freshwater bivalves as resource pulses - Sousa, Ronaldo (2012)
The winter of 2009/2010 was particularly severe in Northern Portugal resulting in higher river flow levels. A study was undertaken to assess the impact of this situation on several populations of freshwater bivalves (e.g., Anodonta anatina, Corbicula fluminea, Margaritifera margaritifera, Potomida littoralis and Unio delphinus) in the catchments of the Rivers Minho, Douro, Taˆ mega, Tua and Sabor. Massive die-offs occurred for all species in all rivers, resulting in the removal of great numbers and biomass from the riverbed to the adjacent riverbanks, reaching maximum values of 2280 individuals.mx2 and 10 225 g wet weight.mx2, respectively. The invasive Asian clam C. fluminea had both highest density and biomass (however, this invasive bivalve is not dominant in several surveyed sites, and some rivers are still not colonized by this species). Results show that the quantitative and qualitative importance of this carrion transfer to the riverbank should be incorporated in future studies on the assessment of ecosystem function, contributing to a better understanding of the role of freshwater bivalves as resource pulses in adjacent terrestrial habitats. Some of the affected species have conservational importance and these extreme climatic events are predicted to increase in the future. These massive die-off events should be incorporated into management plans and selected restoration measures such as rapid relocation of endangered native mussels back to the riverbed can be easily applied to lessen possible impacts.